Sintesis Hidroksiapatit Melalui Precipitated Calcium Carbonate (PCC) Kulit Kerang Darah Dengan Metode Hidrotermal - Jefry Soclin Sianipar; Yelmida Azis; Zultiniar Zultiniar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Hydroxyapatite Ca10(PO4)6(OH)2 is a calcium phosphate compound which is bioactive ceramic material with high bioafinitas and the principal inorganic constituent of bones and teeth. Hydroxyapatite (HAp) materials used as bone implants, adsorbents and catalysts. In this research synthesis of hydroxyapatite can be made by using material which is rich of CaCO3 like PCC blood calm shell with a composition of 95.5% CaCO3. PCC blood calm shell which has calcium source was synthesized to HAp by hydrothermal process with varied rasio Ca/P (1.61, 1.67, and 1.73) and reaction temperature (140oC, 160oC, 180oC, and 200°C). HAp synthesized result has been analyzed using X-ray Diffraction (XRD), scanning electron microscopy (SEM) and Fourier Transform Infrared Spectroscopy (FTIR). The results of FTIR analysis, synthesis of HAp with hydrothermal method through precipitated calcium carbonat (PCC) showed the formation of hydroxyapatite in the presence of peaks PO43- dan OH-. The highest peak is obtained at ratio Ca/P 1.61 at reaction temperature of, 140°C, 160°C, 180°C, and 200°C. XRD diffraction results in hydroxyapatite get the highest purity obtained at ratio Ca/P of 1.61 at temperature of 180°C with a hexagonal crystal structure. The results of SEM-EDX analysis, show that the morphological form of agglomerates or clumping . The molar ratio of Ca/P of hydroxyapatite which is made from sea shells seashell waste through the PCC is 1,77.Keywords : PCC Blood Calm Shell, pH, Temperature, Hydroxyapatite, Hydrothermal Method.